Arrested disproportionation in trivalent, mononuclear, and non-metallocene complexes of Zr(III) and Hf(III) - Grant, Lauren N.; Miehlich, Matthias; Meyer, Karsten; Mindiola, Daniel J. (Chemical Communications, 2018)
Reduction of the group 4 transition metal precursors [(PN)2MCl2] (M = Zr (1), and Hf (2)); PN- = (N-(2-(diisopropylphosphino)-4-methylphenyl)-2,4,6-trimethylanilide), both readily prepared by transmetallation of 2 LiPN with [MCl4(THF)2], with a slight excess of KC8, resulted in the isolation of the trivalent complexes [(PN)2MCl] (M = Zr (3), and Hf (4)). Complexes 1-4 were all identified by solid-state X-ray diffraction analysis, whereas in the case of 3 and 4 low temperature X-band EPR spectroscopy allowed for the identification of these metal-centered d1 radicals. A comparison with the isostructural and isoelectronic but more stable [(PN)2TiCl] is also presented.
CRIS-Team Scopus Importer:2020-09-14